Polyester Resin

A polyester resin with specific compositions and additives addresses the issues of low IV and high ρV in matte films, ensuring high-speed film formation without breakage and maintaining mechanical strength.

JP7600575B2Active Publication Date: 2024-12-17MITSUBISHI CHEM CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2020151440
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-09-09
Publication Date
2024-12-17
Estimated Expiration
2040-09-09

AI Technical Summary

Technical Problem

Existing polyester resins used for matte films face issues with low intrinsic viscosity (IV) leading to film breakage and high volume resistivity (ρV) affecting film forming speed, necessitating a resin with high IV and low ρV to maintain strength and adhesion during high-speed film formation.

Method used

A polyester resin composed of a dicarboxylic acid component with a terephthalic acid component and a diol component with ethylene glycol, having an intrinsic viscosity of 0.80 dL/g or more, a volume resistivity of 10×10⁷ Ω·cm or less, and an intrinsic viscosity reduction rate of less than 10% after melting, achieved by controlling the addition of phosphorus and Group 2 metal compounds.

Benefits of technology

The resin enables high-speed matte film formation without breakage, maintaining mechanical strength and adhesion, while reducing thermal deterioration effects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007600575000001
    Figure 0007600575000001
Patent Text Reader

Abstract

To provide a polyester resin having physical properties suitable for efficiently producing a mat-like film.SOLUTION: A polyester resin comprising dicarboxylic acid components containing terephthalic acid components and diol components containing ethylene glycol satisfies (1), (2) and (3) as follows: (1) an intrinsic viscosity is 0.80dL / g or more; (2) a volume resistivity value in melting at 285°C is 10×107 Ω cm or less; and (3) an inherent viscosity reduction rate from an inherent viscosity IVxdL / g of the polyester resin measured after putting 20 g of the polyester resin (an initial intrinsic viscosity IV0dL / g) into a test tube, soaking it in an oil bath at 180°C in a reduced pressure of 5 Torr or less followed by drying 2.5 hours, and successively melting it at 290°C under a nitrogen gas seal for 1.5 hours, calculated by the following formula is less than 10%. The inherent viscosity reduction rate={(IV0-IVx) / IV0}×100.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polyester resin which exhibits good film-forming properties and excellent strength, and is particularly suitable as a raw material for matte films having a low gloss appearance. [Background technology]

[0002] Polyester films have excellent properties such as mechanical strength, dimensional stability, flatness, heat resistance, chemical resistance, optical properties, etc., and are cost-effective, so they are used in a variety of applications. In particular, there has been an increasing demand for design, especially in digital products such as smartphones, and there is a demand for products to have a matte (matte, low gloss) appearance to give them a high-quality texture. For this reason, it has been proposed to attach a polyester film with a matte surface to a product or to transfer this matte surface to a product.

[0003] Patent Document 1 discloses a polyester film containing a high concentration of inorganic or organic particles as a matte-finish polyester film. As described in Patent Document 1, in order to produce a matte polyester film, it is necessary to add particles at a high concentration. However, adding particles at a high concentration can cause a decrease in strength, such as film breakage, if the intrinsic viscosity (IV) of the polyester resin is low. In addition, since there is a risk of the IV decreasing due to thermal degradation during molding in a molding machine, a polyester resin with a high IV and one that is unlikely to decrease even when subjected to thermal history is required. In addition, if the volume resistivity (ρV) of the polyester resin is high, the electrical adhesion to the cooling roll during film formation of the matte polyester film decreases, and it becomes necessary to reduce the film formation speed (high-speed film formation decreases), which is an inconvenience, so a polyester resin with a relatively low ρV is desired.

[0004] Patent Document 2 discloses a polyester resin having an intrinsic viscosity of 0.70 dl / g or more. However, Patent Document 2 provides a polyester resin for bottles that is environmentally safe, has good color tone, and produces little cyclic trimer as a by-product. However, Patent Document 2 does not recognize the issues necessary for developing a matte polyester film, and does not disclose or suggest ρV or IV reduction rate. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2015-66805 A [Patent Document 2] JP 2001-200044 A Summary of the Invention [Problem to be solved by the invention]

[0006] An object of the present invention is to provide a polyester resin having suitable physical properties for efficiently forming a matte polyester film, that is, a polyester resin having a high intrinsic viscosity (IV), low film breakability, and a low volume resistivity (ρV) that allows a good film formation speed to be achieved. [Means for solving the problem]

[0007] As a result of intensive research, the present inventors have discovered a polyester resin comprising a dicarboxylic acid component containing a terephthalic acid component and a diol component containing ethylene glycol, the polyester resin having an intrinsic viscosity (IV) of 0.80 dL / g or more and a volume resistivity (ρV) of 10×10 when melted at 285° C. 7 The present inventors have discovered that a polyester resin having an intrinsic viscosity of Ω·cm or less and having an intrinsic viscosity reduction rate of less than 10% after melting under specific conditions can solve the above problems, and have completed the present invention. That is, the gist of the present invention lies in the following [1] and [2].

[0008] [1] A polyester resin comprising a dicarboxylic acid component containing a terephthalic acid component and a diol component containing ethylene glycol, the polyester resin satisfying the following (1), (2), and (3): (1) Intrinsic viscosity is 0.80 dL / g or more. (2) The volume resistivity when melted at 285°C is 10 x 10 7 Less than Ω cm. (3) 20 g of the polyester resin (initial intrinsic viscosity IV 0 dL / g) is placed in a test tube, immersed in a 180°C oil bath under reduced pressure of 5 Torr or less, dried for 2.5 hours, and then melted at 290°C for 1 hour and 30 minutes under a nitrogen gas blanket. The intrinsic viscosity IV of the polyester resin is then measured. x The rate of decrease in intrinsic viscosity calculated from dL / g using the following formula is less than 10%. Intrinsic viscosity reduction rate={(IV0-IV x ) / IV0}×100

[0009] [2] The polyester resin according to [1], which is a polyester resin for matte films. Effect of the Invention

[0010] According to the polyester resin of the present invention, a matte polyester film can be formed at high speed without breakage. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] The present invention will be described in detail below. However, the description of the constituent elements described below is one example (representative example) of an embodiment of the present invention, and the present invention is not limited to these contents.

[0012] In the present invention, the polyester resin refers to a polyester resin in which 80% or more of the repeating structural units are ethylene terephthalate units. In addition, in this specification, the symbol "to" indicating a numerical range is used to mean that the numerical values ​​before and after the symbol are included as the lower limit and upper limit.

[0013] [Polyester resin] The polyester resin of the present invention is a polyester resin comprising a dicarboxylic acid component containing a terephthalic acid component and a diol component containing ethylene glycol, and satisfies the following (1), (2), and (3). (1) Intrinsic viscosity (IV) is 0.80 dL / g or more. (2) The volume resistivity (ρV) when melted at 285°C is 10×10 7 Less than Ω cm. (3) 20 g of the polyester resin (initial intrinsic viscosity IV 0 dL / g) is placed in a test tube, immersed in a 180°C oil bath under reduced pressure of 5 Torr or less, dried for 2.5 hours, and then melted at 290°C for 1 hour and 30 minutes under a nitrogen gas blanket. The intrinsic viscosity IV of the polyester resin is then measured. x The rate of decrease in intrinsic viscosity (IV) calculated from dL / g using the following formula is less than 10%. Intrinsic viscosity reduction rate={(IV0-IV x ) / IV0}×100

[0014] (1) Intrinsic viscosity (IV) The intrinsic viscosity (IV) of the polyester resin of the present invention is 0.80 dL / g or more. If the intrinsic viscosity (IV) of the polyester resin is 0.80 dL / g or more, the frequency of breakage during film production is low, which is preferable. The lower limit of the intrinsic viscosity (IV) of the polyester resin of the present invention is preferably 0.82 dL / g, more preferably 0.83 dL / g. The upper limit of the intrinsic viscosity (IV) of the polyester resin of the present invention is not particularly limited, but is preferably 1.00 dL / g. The intrinsic viscosity (IV) of the polyester resin can be controlled by the temperature, pressure, and residence time in the melt polycondensation step during the production of the polyester resin, and by the temperature, pressure, and residence time in the solid-phase polycondensation step, the concentrations of ethylene glycol and water in the inert gas, the shape of the pellets, etc. The intrinsic viscosity (IV) is measured by the method described in the Examples section below.

[0015] (2) Volume resistivity (ρV) The volume resistivity (ρV) of the polyester resin of the present invention when melted at 285°C is 10×107 Ω·cm or less. The volume resistivity (ρV) when melted at 285°C is a physical property necessary for improving the roll adhesion with the molten resin during film formation, and is preferably 9×10 7 Ω·cm or less, preferably 8×10 7 Ω cm or less, more preferably 7×10 7 The lower limit of the volume resistivity (ρV) is not particularly limited, but is preferably 1×10 7 Ω cm. The volume resistivity (ρV) of the polyester resin when melted at 285° C. can be controlled to the above upper limit or less by controlling the amounts of the phosphorus compound and the Group 2 metal compound added during the production of the polyester resin, as described below. The volume resistivity (ρV) is measured by the method described in the Examples section below.

[0016] (3) Intrinsic viscosity (IV) reduction rate The intrinsic viscosity (IV) reduction rate of the polyester resin of the present invention is less than 10%. The decrease in intrinsic viscosity (IV) occurs due to thermal degradation of the polyester resin during molding, and by controlling the amounts of the phosphorus compound and the Group 2 metal compound of the periodic table added during the production of the polyester resin, which will be described later, it is possible to obtain a polyester resin that is less susceptible to decrease in intrinsic viscosity (IV) due to thermal degradation during molding. That is, 20 g of polyester resin (initial intrinsic viscosity IV 0 dL / g) was placed in a test tube, immersed in an oil bath at 180°C under reduced pressure of 5 Torr or less, dried for 2.5 hours, and then melted at 290°C for 1 hour and 30 minutes under a nitrogen gas blanket. The intrinsic viscosity IV of the polyester resin was measured. x From dL / g, it is possible to obtain a polyester resin having an intrinsic viscosity (IV) reduction rate calculated by the following formula of less than 10%. Intrinsic viscosity reduction rate={(IV0-IV x ) / IV0}×100

[0017] (4) Amount of phosphorus compound and compound of metal of Group 2 of the periodic table added In producing the polyester resin of the present invention, the phosphorus compound described below is preferably added so that the phosphorus (P) atom content in the resulting polyester resin is preferably 0.3 to 2.4 mol / ton, more preferably 0.4 to 2.0 mol / ton, and particularly preferably 0.5 to 1.2 mol / ton.

[0018] The phosphorus compound is preferably added so as to satisfy the following formula in accordance with the amount of the Group 2 metal compound of the periodic table to be described later. 0.35≦P / M≦0.60 (In the above formula, P is the number of moles of phosphorus atoms contained per ton of polyester resin, and M is the number of moles of Group 2 metal atoms of the periodic table contained per ton of polyester resin.) If P / M is 0.35 or more, the intrinsic viscosity (IV) of the polyester resin is less likely to decrease due to thermal degradation during molding. If P / M is less than 0.35, the volume resistivity (ρV) of the resulting polyester resin when melted at 285°C is reduced, but the degree of decrease in intrinsic viscosity (IV) increases when the polyester resin is kept molten. If P / M is more than 0.60, the volume resistivity (ρV) of the resulting polyester resin when melted at 285°C is reduced by 10×10 7 The P / M ratio is preferably 0.40 to 0.57, and more preferably 0.45 to 0.55.

[0019] The content of each metal atom in the polyester resin is specifically measured by the method described in the Examples section below.

[0020] [Method of manufacturing polyester resin] The polyester resin of the present invention is basically produced by a conventionally known production method, that is, by the preparation of a raw material slurry, esterification and melt polycondensation, and further the subsequent solid-phase polycondensation.

[0021] <Polyester resin raw material> In the present invention, a dicarboxylic acid component mainly composed of at least one of terephthalic acid and its ester-forming derivatives is subjected to an esterification reaction and / or an ester exchange reaction, followed by a polycondensation reaction, between a diol component mainly composed of ethylene glycol, to obtain a polyester resin of the present invention in which 80% or more of the repeating structural units are ethylene terephthalate units.

[0022] (Dicarboxylic acid component) In the present invention, a dicarboxylic acid component containing terephthalic acid and / or an ester-forming derivative of terephthalic acid (terephthalic acid component) as a main component is used. The content of the terephthalic acid component in the total dicarboxylic acid components used in the present invention is preferably 80 mol% or more, more preferably 90 mol% or more. When the proportion of the terephthalic acid component is equal to or more than the above lower limit, the mechanical strength and heat resistance of the molded product tend to be good in terms of the orientation and crystallization of molecular chains due to stretching when molding into films, bottles, fibers, etc. The upper limit of the proportion of the terephthalic acid component in the total dicarboxylic acid components may be 100 mol%.

[0023] The ester-forming derivatives of terephthalic acid used in the present invention include diesters of alcohols having 1 to 4 carbon atoms, preferably alkyl terephthalates such as dimethyl terephthalate and diethyl terephthalate.

[0024] Examples of dicarboxylic acid components other than the terephthalic acid component used in the present invention include aromatic dicarboxylic acids such as phthalic acid, isophthalic acid, dibromoisophthalic acid, sulfoisophthalic acid, 1,4-phenylenedioxydicarboxylic acid, 4,4'-diphenyldicarboxylic acid, 4,4'-diphenyletherdicarboxylic acid, 4,4'-diphenylketonedicarboxylic acid, 4,4'-diphenoxyethanedicarboxylic acid, 4,4'-diphenylsulfonedicarboxylic acid, and 2,6-naphthalenedicarboxylic acid; alicyclic dicarboxylic acids such as hexahydroterephthalic acid and hexahydroisophthalic acid; and aliphatic dicarboxylic acids such as succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, undecadicarboxylic acid, and dodecadicarboxylic acid; and ester-forming derivatives of these dicarboxylic acids. The dicarboxylic acid component may be used alone or in combination of two or more of the above.

[0025] (Diol component) In the present invention, a diol component containing ethylene glycol as a main component is used. The content of ethylene glycol in the total diol components used in the present invention is preferably 80 mol% or more, more preferably 90 mol% or more, and particularly preferably 95 mol% or more. When the proportion of ethylene glycol is equal to or more than the above lower limit, the mechanical strength and heat resistance of the molded product tend to be good in terms of the orientation and crystallization of molecular chains due to stretching when molding into films, bottles, fibers, etc. The upper limit of the proportion of ethylene glycol in the total diol components may be 100 mol%.

[0026] Examples of the diol component other than ethylene glycol used in the present invention include aliphatic diols such as diethylene glycol, trimethylene glycol, tetramethylene glycol, pentamethylene glycol, hexamethylene glycol, octamethylene glycol, decamethylene glycol, neopentyl glycol, 2-ethyl-2-butyl-1,3-propanediol, polyethylene glycol, and polytetramethylene ether glycol; 1,2-cyclohexanediol, 1,4-cyclohexanediol, 1,1-cyclohexanedimethylol, and the like. Examples of the diol component include alicyclic diols such as xylylene glycol, 4,4'-dihydroxybiphenyl, 2,2-bis(4'-hydroxyphenyl)propane, 2,2-bis(4'-β-hydroxyethoxyphenyl)propane, bis(4-hydroxyphenyl)sulfone, and bis(4-β-hydroxyethoxyphenyl)sulfonic acid; and ethylene oxide or propylene oxide adducts of 2,2-bis(4'-hydroxyphenyl)propane. The diol component may be one of the above, or two or more of them may be used in combination.

[0027] (Copolymerization components other than dicarboxylic acid components and diol components) In the present invention, in addition to the diol component and dicarboxylic acid component, other copolymerizable components may be used as polyester resin raw materials. Examples of other copolymerizable components include hydroxycarboxylic acids and alkoxycarboxylic acids such as glycolic acid, p-hydroxybenzoic acid, and p-β-hydroxyethoxybenzoic acid, monofunctional components such as stearyl alcohol, heneicosanol, octacosanol, benzyl alcohol, stearic acid, behenic acid, benzoic acid, t-butylbenzoic acid, and benzoylbenzoic acid, and polyfunctional components having three or more functional groups such as tricarballylic acid, trimellitic acid, trimesic acid, pyromellitic acid, naphthalenetetracarboxylic acid, gallic acid, trimethylolethane, trimethylolpropane, glycerol, pentaerythritol, and sugar ester. One or more of these other copolymerizable components can be used within a range that does not impair the effects of the present invention.

[0028] <Catalysts and assistants> In the production of the polyester resin of the present invention, a catalyst and an auxiliary can be used in the esterification reaction, the ester exchange reaction, and the melt polycondensation reaction.

[0029] (Catalyst in esterification or transesterification reaction) In the esterification reaction or transesterification reaction, the same catalysts and assistants as those used in the polycondensation described below can be used. However, in the esterification reaction, the reaction proceeds without using these catalysts, so there is no need to add a catalyst.

[0030] Examples of the catalyst include antimony compounds such as diantimony trioxide, antimony acetate, antimony tartrate, potassium antimony tartrate, antimony oxychloride, antimony glycolate, antimony pentoxide, and triphenylantimony; germanium compounds such as germanium dioxide and germanium tetroxide; titanium compounds such as titanium alcoholates such as tetramethyl titanate, tetraisopropyl titanate, and tetrabutyl titanate, and titanium phenolates such as tetraphenyl titanate; compounds of Group 2 metals in the periodic table such as magnesium compounds such as magnesium acetate, magnesium hydroxide, magnesium carbonate, magnesium oxide, magnesium alkoxide, and magnesium hydrogen phosphate, and calcium compounds such as calcium acetate, calcium hydroxide, calcium carbonate, calcium oxide, calcium alkoxide, and calcium hydrogen phosphate; manganese compounds such as manganese oxide, manganese hydroxide, and manganese acetate; and zinc compounds.

[0031] These catalysts may be used alone or in combination of two or more. Among these catalysts, from the viewpoints of reactivity, solubility in the reaction system, coloration of the obtained polyester resin, etc., preferred are antimony compounds and Group 2 metal compounds of the periodic table, more preferred are antimony compounds and magnesium compounds, and particularly preferred are diantimony trioxide and magnesium acetate.

[0032] (Melt polycondensation reaction catalyst) As the melt polycondensation reaction catalyst used in producing the polyester resin in the present invention, the above-mentioned esterification reaction or transesterification reaction catalyst may be used as it is as the melt polycondensation reaction catalyst, or the above catalyst may be further added. Among the melt polycondensation reaction catalysts, from the viewpoints of polycondensation activity, thermal stability of the resulting polyester resin, and ease of availability, antimony compounds are preferred, and diantimony trioxide is particularly preferred. Although germanium compounds are easy to obtain resins with good color tone, the resulting polyester resins tend to have poor thermal stability. Furthermore, germanium compounds are relatively expensive. Titanium compounds tend to result in poor thermal stability of the resulting polyester resins.

[0033] (Amount of catalyst added) The amounts of the esterification reaction catalyst or transesterification reaction catalyst and the melt polycondensation reaction catalyst added are not particularly limited, but they are preferably added so that the catalyst-derived metal concentration in the resulting polyester resin falls within the following range. For example, the amount of the antimony compound is preferably 1.0 to 2.5 mol / ton, more preferably 1.4 to 2.4 mol / ton, and particularly preferably 1.6 to 2.2 mol / ton in terms of antimony atoms relative to the resulting polyester resin. When a Group 2 metal compound of the periodic table is used, the amount of metal atom relative to the resulting polyester resin is preferably 0.4 to 1.7 mol / ton, more preferably 0.6 to 1.5 mol / ton, and particularly preferably 0.8 to 1.2 mol / ton.

[0034] (Heat stabilization aid) In the esterification reaction, the ester exchange reaction and the melt polycondensation reaction, a phosphorus compound can be added as a heat stabilizing aid in addition to the catalyst. Examples of the phosphorus compound include orthophosphoric acid; polyphosphoric acid; phosphoric acid esters such as trimethyl phosphate, triethyl phosphate, tri-n-butyl phosphate, trioctyl phosphate, triphenyl phosphate, methyl acid phosphate, ethyl acid phosphate, isopropyl acid phosphate, and butyl acid phosphate; pentavalent phosphorus compounds such as ethyl diethyl phosphonoacetate; phosphorous acid, hypophosphorous acid, and trivalent phosphorus compounds such as trimethyl phosphite, diethyl phosphite, triethyl phosphite, tris-dodecyl phosphite, tris-nonyl decyl phosphite, and triphenyl phosphite. These phosphorus compounds may be used alone or in combination of two or more. Among these, from the viewpoint of controlling the polycondensation rate, it is preferable to use pentavalent phosphorus compounds such as phosphoric acid and phosphoric esters, and more specifically, trimethyl phosphate and ethyl acid phosphate are more preferably used.

[0035] When a phosphorus compound is used, it can be added at any time up to the start of the melt polycondensation reaction. The phosphorus compound may be added when preparing a slurry of the dicarboxylic acid component and the diol component, may be added to an esterification reaction tank, may be added to a polycondensation reaction tank, or may be added to a transfer pipe therefor, but it is preferable to add it at the initial stage of the reaction, i.e., when preparing the slurry, since this does not reduce the activity of the polycondensation catalyst.

[0036] The phosphorus compound is added so that the phosphorus atom content and P / M of the resulting polyester resin satisfy the above-mentioned preferred values.

[0037] (Other Auxiliaries) In the esterification reaction, the above-mentioned catalyst and auxiliary can be used during melt polycondensation. At that time, for example, by adding a small amount of other auxiliary, such as a tertiary amine such as triethylamine, tri-n-butylamine, benzyldimethylamine, etc.; a quaternary ammonium hydroxide such as tetraethylammonium hydroxide, tetra-n-butylammonium hydroxide, trimethylbenzylammonium hydroxide, etc.; or a basic compound such as lithium carbonate, sodium carbonate, potassium carbonate, sodium acetate, etc., the by-production of diethylene glycol from ethylene glycol can be suppressed.

[0038] <Method of producing polyester resin> The method for producing the polyester resin of the present invention will be described below by taking as an example a method for producing polyethylene terephthalate, which is a polyester resin raw material containing ethylene glycol as a main component of the diol component and terephthalic acid as a main component of the dicarboxylic acid component. The method for producing the polyester resin of the present invention is carried out by a raw material preparation step, an esterification step in which an esterification reaction or an ester exchange reaction is carried out, a melt polycondensation step, and a subsequent solid phase polycondensation step.

[0039] (Raw material preparation process) In the raw material preparation step, a dicarboxylic acid component mainly composed of a terephthalic acid component and a diol component mainly composed of ethylene glycol are charged into a slurry preparation tank together with other copolymerization components used as necessary, mixed under stirring, and filtered as necessary to obtain a raw material slurry. The diol component is mixed so that the molar ratio of the dicarboxylic acid component to the dicarboxylic acid component is preferably 1.0 to 2.0, more preferably 1.05 to 1.5, and particularly preferably 1.1 to 1.4. By keeping this molar ratio within this range, a sufficient esterification reaction rate can be obtained while suppressing the amount of diethylene glycol produced from ethylene glycol.

[0040] When the terephthalic acid component is an ester-forming derivative having a melting point, such as dimethyl terephthalate, the ester-forming derivative can be melted and stored as a raw material, and if necessary, filtered and fed to the esterification step separately from ethylene glycol. The molar ratio of ethylene glycol to the ester-forming derivative is preferably 1.5 to 2.5, more preferably 1.7 to 2.3, and particularly preferably 1.9 to 2.1. If this molar ratio is less than the lower limit, the transesterification reactivity will decrease, while if it exceeds the upper limit, the amount of diethylene glycol produced from ethylene glycol will increase.

[0041] (Esterification process) The esterification step is a step in which an oligomer is obtained by carrying out an esterification reaction between terephthalic acid and ethylene glycol and / or a transesterification reaction between a terephthalic acid ester-forming derivative and ethylene glycol. The esterification reaction is carried out in a single esterification reaction tank or a multi-stage reaction apparatus in which a plurality of esterification reaction tanks are connected in series, under reflux of ethylene glycol, while removing water produced in the reaction and excess ethylene glycol from the system, until the esterification rate (the proportion of carboxyl groups in the raw dicarboxylic acid component that have reacted with the diol component and been esterified) reaches usually 90% or more, preferably 93% or more. The number average molecular weight of the polyester low molecular weight substance (oligomer) as the esterification reaction product is preferably 500 to 5,000.

[0042] Regarding reaction conditions for the esterification reaction, in the case of using a plurality of esterification reaction tanks, the reaction temperature in the first stage esterification reaction tank is usually 240 to 270°C, preferably 245 to 270°C, and the pressure is usually 0 to 300 kPaG (G indicates a relative pressure to atmospheric pressure), preferably 0 to 200 kPaG, and in the final stage, the reaction temperature is usually 250 to 280°C, preferably 255 to 275°C, and the pressure is usually 0 to 180 kPaG, preferably 0 to 150 kPaG. In the case of using a single esterification reaction tank, the reaction temperature is usually 200 to 280°C, preferably 210 to 270°C, and the pressure is usually 0 to 180 kPaG, preferably 0 to 150 kPaG.

[0043] In the esterification step, ethylene glycol may be added during the esterification reaction in order to adjust the amount of terminal carboxyl groups in the polyester resin after melt polycondensation. The amount of ethylene glycol added in the esterification step is preferably 50 to 1300 mol / ton based on the amount of prepolymer produced. If a large amount of ethylene glycol is added that exceeds this upper limit, the load on the distillation system of the polycondensation reaction increases. The amount of ethylene glycol added is more preferably 100 to 1150 mol / ton.

[0044] The timing of adding ethylene glycol is the latter stage of the esterification step, and it is preferable to add it after the esterification rate exceeds 50%, preferably 60% or more, more preferably 80% or more, and particularly preferably 90% or more, because adding ethylene glycol to an oligomer with an esterification rate of less than 50% has a low effect of controlling the amount of terminal carboxyl groups.

[0045] In the case of the transesterification reaction, a single transesterification reaction tank or a multi-stage reaction apparatus in which a plurality of transesterification reaction tanks are connected in series is used to carry out the reaction under typical polyester resin production conditions while refluxing ethylene glycol and removing the alcohol component derived from the ester produced in the reaction and excess ethylene glycol from the system. The number average molecular weight of the resulting low molecular weight polyester (oligomer) as the transesterification reaction product is preferably 500 to 5,000.

[0046] Regarding reaction conditions in the transesterification reaction, in the case of using a plurality of transesterification reaction tanks, the reaction temperature in the first transesterification reaction tank is usually 180 to 230°C, preferably 180 to 220°C, and the pressure is usually 0 to 300 kPaG, preferably 0 to 200 kPaG, and in the final stage, the reaction temperature is usually 220 to 260°C, preferably 225 to 240°C, and the pressure is usually 0 to 200 kPaG, preferably 0 to 150 kPaG. When using a single transesterification reaction tank, the reaction temperature in the transesterification reaction tank is usually 150 to 280°C, preferably 150 to 250°C, and the pressure is usually 0 to 200 kPaG, preferably 0 to 150 kPaG.

[0047] (Melt polycondensation process) In the present invention, the esterification reaction or transesterification reaction step is followed by a melt polycondensation step in which the oligomer is melt polycondensed to obtain a polyester resin. The melt polycondensation may be performed by either a continuous or batch method, but in the case of a continuous method, the melt polycondensation is performed using a reaction apparatus in which a plurality of polycondensation reaction tanks are connected in series, for example, a multi-stage reaction apparatus consisting of a first stage reactor of a complete mixing type equipped with an agitator, and second and third stages of horizontal plug-flow type reactors equipped with an agitator, while the by-produced ethylene glycol is distilled out of the system under reduced pressure.

[0048] As reaction conditions in continuous melt polycondensation, in the case of a plurality of polycondensation reaction tanks, the reaction temperature in the first stage polycondensation reaction tank is usually 250 to 290°C, preferably 260 to 280°C, and the absolute pressure is usually 65 to 1.3 kPa, preferably 26 to 2 kPa, and the reaction temperature in the final stage is usually 265 to 300°C, preferably 270 to 295°C, and the absolute pressure is usually 1.3 to 0.013 kPa, preferably 0.65 to 0.065 kPa. As reaction conditions in the intermediate stage polycondensation reaction tank, intermediate conditions between these are selected. For example, in a three-stage reactor, the reaction temperature in the second stage is usually 265 to 295°C, preferably 270 to 285°C, and the absolute pressure is usually 6.5 to 0.13 kPa, preferably 4 to 0.26 kPa.

[0049] On the other hand, in the case of the batch process, a reaction apparatus consisting of an esterification reaction tank or an ester exchange reaction tank and a polycondensation reaction tank connected in series thereto is usually used, and the reaction is carried out under reduced pressure while distilling off the by-produced ethylene glycol from the system.

[0050] As reaction conditions for the batch-wise melt polycondensation, the reaction temperature in the polycondensation reaction tank is gradually increased usually within the range of 220 to 300°C, preferably 220 to 295°C, while gradually reducing the pressure until the final pressure is usually 1.3 to 0.013 kPa, preferably 0.65 to 0.065 kPa.

[0051] (Pelletization) The product of the melt polycondensation process (sometimes referred to as polyester resin prepolymer) is pelletized by either flowing in the form of strands in the air through a die in a molten state, immediately bringing it into contact with cooling water to solidify, and then cutting it with a cutter, a so-called strand cutting method, or by flowing the molten resin directly into cooling water through a die, and cutting it with a cutter provided in front of the die to pelletize it, a so-called underwater cutting method.

[0052] (Solid phase polycondensation process) The polyester resin pellets after the melt polycondensation are preferably subjected to solid-phase polycondensation in order to adjust the intrinsic viscosity to a desired range. The solid-phase polycondensation can be carried out by either a continuous method or a batch method.

[0053] For example, in a continuous solid-phase polycondensation step, it is preferable to carry out solid-phase polycondensation by heating in a flow of an inert gas such as nitrogen, carbon dioxide, or argon at a pressure of usually 100 kPaG or less, preferably 20 kPaG or less, for usually about 5 to 30 hours, with the lower limit being usually 190°C, preferably 195°C, and the upper limit being usually 230°C, preferably 225°C.

[0054] On the other hand, in the batch-type solid-phase polycondensation step, for example, solid-phase polycondensation is carried out by heating under a flow of an inert gas such as nitrogen, carbon dioxide, or argon at a pressure of usually 100 kPaG or less, preferably 20 kPaG or less, for usually about 4 to 30 hours, at a temperature of usually 190° C., preferably 195° C., and usually 230° C., preferably 225° C. Alternatively, it is preferable to carry out solid-phase polycondensation by heating under a reduced pressure of, for example, an absolute pressure of usually 0.013 kPa, preferably 0.065 kPa, and usually 6.5 kPa, for usually about 1 to 25 hours, preferably about 1 to 20 hours, at a temperature of usually 190° C., preferably 195° C., and usually 235° C., more preferably 230 to 232° C.

[0055] By adjusting the degree of polymerization in this manner, a polyester resin having an intrinsic viscosity (IV) of 0.80 dL / g or more can be obtained.

[0056] Before being subjected to the solid-phase polycondensation step, the pellets may be pre-crystallized at a temperature lower than the temperature at which the solid-phase polycondensation is carried out. For example, the pellets may be heated in a dry state at 120 to 200°C, preferably 130 to 190°C, for about 1 minute to 4 hours, or the pellets may be heated in an atmosphere containing water vapor at 120 to 200°C for 1 minute or more, and then subjected to the solid-phase polycondensation.

[0057] [Polyester resin composition] The polyester resin of the present invention may be added with various particles, additives, and resins other than polyester resins described below to form a polyester resin composition.

[0058] <particle> When the polyester resin of the present invention is formed into a film, it is preferable to add inorganic and / or organic particles so as to impart a low gloss appearance to the film. The above particles are not particularly limited as long as they are particles capable of imparting a matte finish.

[0059] Examples of inorganic particles include calcium carbonate, barium sulfate, alumina, silica, talc, titania, kaolin, mica, zeolite, and the like, as well as surface-treated particles of these particles with a silane coupling agent, a titanate coupling agent, or the like. Examples of the organic particles include resin particles such as acrylic resin, styrene resin, and crosslinked resin. These particles may be used alone or in combination of two or more kinds.

[0060] The particle size of these particles is preferably in the range of 2.0 to 10.0 μm, more preferably 3.0 to 8.0 μm, and particularly preferably 4.0 to 6.0 μm, in terms of average particle size. The amount of these particles added is preferably from 3 to 10% by mass, more preferably from 4 to 10% by mass, and particularly preferably from 6 to 8% by mass, based on the polyester resin. These particles can be added during or after the melt polycondensation.

[0061] <Additives> The polyester resin of the present invention may contain other conventional additives as necessary. Examples of the other additives include antioxidants, ultraviolet absorbers, light stabilizers, antistatic agents, lubricants, antiblocking agents, antifogging agents, nucleating agents, plasticizers, and colorants. These additives may be used alone or in combination of two or more. The amount of the other additives added is usually 5% by mass or less, preferably 0.05 to 2% by mass, based on the polyester resin. These additives can be added during or after the melt polycondensation.

[0062] (Blending method) The method of blending the various particles and additives is not particularly limited, but a method using a single-screw or twin-screw extruder having a vent port for volatilization as a kneader is preferred. Each component, including the additional component, may be fed to the kneader all at once or sequentially. Also, two or more components selected from each component, including the additional component, may be mixed in advance.

[0063] [Polyester resin film] The polyester resin of the present invention is preferably used for film or sheet formation, more preferably for film formation. The film formation method is not particularly limited, and a known method can be used. For example, the polyester resin is melted at a temperature equal to or higher than its melting point, and then a polyester resin sheet is obtained by extrusion molding, and the obtained polyester resin sheet is then biaxially stretched to obtain a polyester resin film.

[0064] More specifically, the polyester resin of the present invention is melt-extruded into a film at 250 to 320° C., solidified to form an amorphous sheet, and then sequentially or simultaneously biaxially stretched in the longitudinal and transverse directions at 70 to 140° C., and the resulting film is heat-treated at 160 to 240° C. In general, the stretching temperature is preferably 80 to 140° C., and the stretching ratio is selected from the range of 2 to 7 times in the longitudinal and transverse directions.

[0065] The thickness of the polyester resin film thus formed is usually preferably about 1 to 300 μm, more preferably 5 to 125 μm, and even more preferably 8 to 100 μm.

[0066] According to the polyester resin of the present invention, a matte polyester film can be produced at high speed by such a method without causing breakage of the film. EXAMPLES

[0067] The present invention will be described in more detail below with reference to examples. However, the present invention is not limited to the following examples as long as it does not depart from the gist of the present invention.

[0068] The samples (esterification reaction products, polyester resin prepolymers, or polyester resins) were measured and evaluated by the following measurement methods.

[0069] <Metal atom content: moles / ton> 2.5 g of the sample was incinerated and completely decomposed using standard methods with hydrogen peroxide in the presence of sulfuric acid, and then the volume was adjusted to 5 mL with distilled water. The metal atoms were quantified using a plasma emission spectrometer (JOBIN YVON ICP-AES "JY46P" model) and converted to moles / ton in the sample.

[0070] <Volume resistivity when melted (ρV): Ω cm> 15 g of the sample was placed in a test tube with an inner diameter of 20 mm and a length of 180 mm. The inside of the tube was thoroughly replaced with nitrogen, and then the tube was immersed in an oil bath at 250°C and the inside of the tube was reduced to 1 Torr or less using a vacuum pump for 20 minutes for vacuum drying. The oil bath temperature was then raised to 285°C to melt the sample, after which nitrogen pressure was restored and reduced repeatedly to remove any air bubbles that were mixed in. A sample with an area of ​​1 cm2 was placed in the melt. 2 Two stainless steel electrodes were inserted in parallel with a gap of 5 mm (the opposing back sides were covered with an insulator), and after the temperature stabilized, a DC voltage of 100 V was applied using a resistance meter (Hewlett-Packard "MODEL HP4339 B"), and the resistance value at that time was calculated to obtain the volume resistivity (ρV: Ω cm).

[0071] <Intrinsic viscosity (IV): dL / g> Approximately 0.25 g of the freeze-pulverized polyester resin sample was dissolved in approximately 25 mL of a mixed solvent of phenol / 1,1,2,2-tetrachloroethane (mass ratio 1 / 1) at 120°C for 30 minutes to a concentration of 1.00 g / dL, and then cooled to 30°C. The number of seconds it took for the sample solution and the solvent alone to fall was measured at 30°C using a fully automatic solution viscometer (DT553, manufactured by Sentec Co., Ltd.), and the intrinsic viscosity (IV) was calculated using the following formula. IV=((1+4K H η sp ) 0.5 -1) / (2K H C) Here, η sp = η / η0-1, where η is the time it takes for the sample solution to fall, η0 is the time it takes for the solvent alone to fall, C is the concentration of the sample solution (g / dL), and K H is Huggins' constant. K H was set to 0.33. When measuring the intrinsic viscosity of the polyester resin prepolymer, the prepolymer was used in pellet form without freeze-pulverization, and the dissolution conditions were 110° C. and 30 minutes.

[0072] <Intrinsic viscosity (IV) reduction rate:%> The intrinsic viscosity measured by the above method: IV0 dL / g A polyester resin sample of 21 g was placed in a test tube with a branch tube, immersed in an oil bath at 180°C under a reduced pressure of 1 Torr or less, and dried for 2.5 hours, after which the pressure was restored with nitrogen gas and the sample was removed from the oil bath while still sealed with nitrogen gas. The temperature of the oil bath was set to 290°C, and the test tube was immersed in the oil bath while still sealed with nitrogen gas, to melt the dried sample. After immersing in the oil bath for 1 hour and 30 minutes, the sample was removed and rapidly cooled to an amorphous state. The sample was cut to an appropriate size with nippers or the like, and the intrinsic viscosity (IV x The decrease rate of intrinsic viscosity (IV) was calculated according to the following formula and evaluated according to the following criteria. Intrinsic viscosity (IV) reduction rate = {(IV0-IV x ) / IV0}×100 (Evaluation Criteria) 〇: IV reduction rate less than 10% △: IV reduction rate 10% to less than 15% ×: IV reduction rate 15% or more

[0073] <Evaluation of film adhesion under static electricity application> The film formability of the polyester film was evaluated according to the following criteria. (Evaluation Criteria) ⊚: Very good film-forming properties are shown. ◯: The film-forming property is worse than ◯, but film formation is possible. ×: Poor film-forming properties.

[0074] <Evaluation of breakability during film formation> The frequency of breakage during the production of the polyester film was evaluated according to the following criteria. (Evaluation Criteria) ○: Less than once a day △: 1 to 3 times per day ×: 3 or more times a day

[0075] [Example 1] <Production of polyester resin> The continuous polyester resin production equipment used was equipped with a slurry preparation tank equipped with an agitator, an ethylene glycol charging pipe, and a terephthalic acid charging pipe; each pipe for transferring the slurry and the esterification reaction product to each esterification reaction tank; complete mixing type first and second stage esterification reaction tanks equipped with an agitator, a separation tower, a raw material receiving port, a catalyst charging pipe, and a reactant transfer pipe; a pipe for transferring the esterification reaction product (oligomer) to the melt polycondensation reaction tank; a complete mixing type first stage melt polycondensation reaction tank equipped with an agitator, a separation tower, an oligomer receiving port, and a catalyst charging pipe; plug flow type second and third stage melt polycondensation reaction tanks equipped with an agitator, a separation tower, a polymer receiving port, and a polymer withdrawal port; and a pelletizer that removes the prepolymer from the withdrawal port in the form of strands through a die plate via a gear pump and cuts the strands under water cooling.

[0076] Using the above-mentioned polyester resin continuous production apparatus, a polyester resin prepolymer in a molten state obtained by esterifying a dicarboxylic acid with a diol and then melt-polycondensing the diol was taken out of a die plate in the form of a strand and cut to produce polyester resin pellets.

[0077] An ethylene glycol solution of ethyl acid phosphate (concentration: 7.8% by mass) at 0.50 mol / ton in terms of phosphorus atom relative to the polyester resin to be produced, terephthalic acid and ethylene glycol were supplied to a slurry preparation tank so that the ratio of terephthalic acid:ethylene glycol was 166:87 (mass ratio) (molar ratio: 1:1.4) to prepare a slurry.

[0078] The first-stage esterification reaction tank was maintained at a temperature of 265°C under a nitrogen atmosphere and at a relative pressure of 120 kPaG with respect to atmospheric pressure. The slurry prepared in the slurry preparation tank was continuously supplied thereto so that the average residence time of the reactants was 4.5 hours. The esterification reaction was carried out while distilling off the water produced in the separation tower, and the reactants were continuously transferred to the second-stage esterification reaction tank. In the second-stage esterification reaction tank, the esterification reaction was carried out at a temperature of 260°C, a pressure of 0 kPaG, and an average residence time of 1.2 hours, and the product was continuously transferred to the complete mixing-type first-stage melt polycondensation reaction tank through a transfer pipe. During the transfer, an ethylene glycol solution of magnesium acetate tetrahydrate (concentration 6.4% by mass) was continuously added to the esterification reaction product at a magnesium atom amount of 1.06 mol / ton relative to the polyester resin produced, and further an ethylene glycol solution of diantimony trioxide (concentration 2.0% by mass) was continuously added at a magnesium atom amount of 1.96 mol / ton relative to the polyester resin produced.

[0079] In the first-stage melt polycondensation reaction tank, the reaction was carried out at a temperature of 270°C, under an absolute pressure of 2.6 kPa, with an average residence time of 70 minutes, and the reaction product was continuously transferred to the second-stage melt polycondensation reaction tank through a transfer pipe. In the second-stage melt polycondensation reaction tank, the melt polycondensation reaction was carried out at a temperature of 278°C, under an absolute pressure of 0.5 kPa, for a residence time of 70 minutes, and the reaction product was continuously transferred to the third-stage melt polycondensation reaction tank through a transfer pipe. In the third-stage melt polycondensation reaction tank, a melt polycondensation reaction was carried out at a temperature of 280° C., under an absolute pressure of 0.3 kPa, for an average residence time of 80 minutes, to obtain a polyester resin.

[0080] The polyester resin was extruded from a die in the form of strands, cooled and solidified, and cut into pellets with a cutter. The inherent viscosity of the pellets was 0.65 dL / g. This polyester resin is called a polyester resin prepolymer. 5,000 kg of the obtained polyester resin prepolymer was charged into a double-cone type solid-phase polycondensation apparatus equipped with a nitrogen inlet, a heater, a thermometer, a pressure gauge, and a pressure reduction exhaust port, and the resin temperature was adjusted to 160°C and the absolute pressure to 0.07 kPa, and the mixture was vacuum-dried for 2.5 hours. Subsequently, the resin temperature was increased to 232°C and solid-phase polycondensation was carried out for 12 hours to obtain a polyester resin. The physical properties of the obtained polyester resin are shown in Table 1. Furthermore, when the melt thermal stability was evaluated, the IV reduction rate was 7%, which was good.

[0081] <Film manufacturing> The polyester resin obtained above was blended with 8% by mass of alkyl methacrylate-styrene copolymer particles having an average particle size of 4.5 μm, and melt-extruded at 290° C. using a vented twin-screw extruder. The sheet was cast onto a cooling roll with a surface temperature set at 25° C. using an electrostatic adhesion method to obtain an unstretched sheet. The sheet was then stretched 3.2 times in the machine direction at 90° C., introduced into a tenter, stretched 4.2 times in the transverse direction at 130° C., and further heat-treated at 240° C. to obtain a polyester film having a thickness of 50 μm. The evaluation results of the film formability of the film are shown in Table 1. The polyester resin obtained in Example 1 had a low volume resistivity and a high intrinsic viscosity, and was therefore suitable for producing a matte polyester film.

[0082] [Example 2] A polyester resin was obtained in the same manner as in Example 1, except that the amounts of diantimony trioxide and ethyl acid phosphate added were changed as shown in Table 1. The physical properties of the obtained polyester resin are shown in Table 1. A polyester film was produced using the obtained polyester resin in the same manner as in Example 1. The evaluation results of the film formability of the film are shown in Table 1. The polyester resin thus obtained had a low volume resistivity and a high intrinsic viscosity, and was therefore suitable for producing a matte polyester film.

[0083] [Comparative Example 1] A polyester resin was obtained in the same manner as in Example 2, except that the amount of ethyl acid phosphate added was changed as shown in Table 1. The physical properties of the obtained polyester resin are shown in Table 1. A polyester film was produced using the obtained polyester resin in the same manner as in Example 1. The evaluation results of the film formability of the film are shown in Table 1. The resulting polyester resin had a high volume resistivity and was therefore unsuitable for forming a film.

[0084] [Comparative Example 2] A polyester resin was obtained in the same manner as in Example 1, except that the amount of ethyl acid phosphate added in Example 1 was as shown in Table 1, the intrinsic viscosity of the polyester resin prepolymer was 0.62 dL / g, and the solid-phase polymerization conditions were as shown in Table 1. The physical properties of the obtained polyester resin are shown in Table 1. A polyester film was produced in the same manner as in Example 1 using the obtained polyester resin. The evaluation results of the film formability of the film are shown in Table 1. The resulting polyester resin had a low intrinsic viscosity and was therefore unsuitable for forming a film.

[0085] [Comparative Example 3] A polyester resin was obtained in the same manner as in Example 1, except that the amounts of magnesium acetate tetrahydrate and ethyl acid phosphate added in Example 1 were changed as shown in Table 1, and the intrinsic viscosity of the polyester resin prepolymer was changed as shown in Table 1. The physical properties of the obtained polyester resin are shown in Table 1. A polyester film was produced in the same manner as in Example 1 using the obtained polyester resin. The evaluation results of the film formability of the film are shown in Table 1. The resulting polyester resin had a high volume resistivity and a low intrinsic viscosity, making it unsuitable for forming a film.

[0086] [Comparative Example 4] A polyester resin was obtained in the same manner as in Example 1, except that the amounts of magnesium acetate tetrahydrate and ethyl acid phosphate added in Example 1 were changed as shown in Table 1, and the intrinsic viscosity of the polyester resin prepolymer was changed as shown in Table 1. The physical properties of the obtained polyester resin are shown in Table 1. A polyester film was produced in the same manner as in Example 1 using the obtained polyester resin. The evaluation results of the film formability of the film are shown in Table 1. The resulting polyester resin had a large decrease in intrinsic viscosity and was therefore unsuitable for film formation.

[0087] [Table 1] [Industrial Applicability]

[0088] The polyester resin of the present invention has a low volume resistivity that allows film formation at a high film formation rate, and an intrinsic viscosity suitable for forming a matte film. Therefore, the polyester resin of the present invention is particularly suitable as a raw material for a matte polyester film.

Claims

1. A polyester resin comprising a dicarboxylic acid component containing a terephthalic acid component and a diol component containing ethylene glycol, the polyester resin satisfying the following (1), (2), and (3): (1) Intrinsic viscosity is 0.80 dL / g or more. (2) The volume resistivity when melted at 285°C is 10 x 10 7 Ω・cm or less. (3) The polyester resin (initial intrinsic viscosity IV 0 The intrinsic viscosity (IV) of the polyester resin is measured after 20 g of the polyester resin is placed in a test tube, immersed in an oil bath at 180° C. under a reduced pressure of 5 Torr or less, dried for 2.5 hours, and then melted at 290° C. for 1 hour and 30 minutes under a nitrogen gas blanket. x The rate of decrease in intrinsic viscosity calculated from dL / g using the following formula is less than 10%. Intrinsic viscosity reduction rate = {(IV 0 -IV x ) / IV 0 }×100

2. 2. The polyester resin according to claim 1, which is a polyester resin for a matte film.

Citation Information

Patent Citations

  • Polyester composition

    JP1992270727A

  • Polyester resin

    JP2001200044A

  • Polyester resin

    JP2010163613A

  • Method for producing polyester composition

    JP2013189521A

  • Biaxially orientated polyester film for mold release

    JP2015066805A